Analysis of the effect of return on equity (roe) and company size on dividend per share (dps) in state-owned banks for the 2017-2021 period - Simanullang, Sairun; Simanullang, Fransiska (IHSA Institute, 2023)
This study aims to determine how much influence Return On Equity (ROE) and Company Size have on Dividend Per Share (DPS) in BUMN-Owned Banking for the 2017-2021 period, both partially and simultaneously. The method used in this research is quantitative data. The sample used is financial reports from 2017-2021. While the analysis technique used is descriptive analysis, classical assumption test, multiple regression analysis, regression coefficient and coefficient of determination. Based on the results of research on Bank Mandiri, BNI and BRI obtained the results of the F Test, amounting to 8.985 > 3.58 with a significance value of 0.004 <0.05 so that simultaneously Return On Equity (ROE) and Company Size have a significant and significant effect on Dividend Per Share with a relationship percentage of 82.5%. Based on the results of the partial T-test Return On Equity (ROE) on Dividend Per Share, a value of 2.079 <2.201 is obtained with a significant value of 0.060 > 0.05. percentage of 59.2%. The results of the partial T-test for Company Size on Dividend Per Share obtained a value of 3.673> 2.201 with a significant value of 0.003 <0.05. The results indicated that there was a significant effect of Company Size on Dividend Per Share with a percentage of 72.7%